Relationship Between Malpractice Litigation Pressure and Rates of Cesarean Section and Vaginal Birth After Cesarean Section - Yang, Y. Tony (2009)
BACKGROUND: Since the 1990s, nationwide rates of vaginal birth after cesarean section (VBAC) have decreased sharply and rates of cesarean section have increased sharply. Both trends are consistent with clinical behavior aimed at reducing obstetricians’ exposure to malpractice litigation. OBJECTIVE: To estimate the effects of malpractice pressure on rates of VBAC and cesarean section. RESEARCH DESIGN, SUBJECTS, MEASURES: We used state-level longitudinal mixed-effects regression models to examine data from the Natality Detail File on births in the United States (1991–2003). Malpractice pressure was measured by liability insurance premiums and tort reforms. Outcome measures were rates of VBAC, cesarean section, and primary cesarean section. RESULTS: Malpractice premiums were positively associated with rates of cesarean section (β = 0.15, P = 0.02) and primary cesarean section (β = 0.16, P = 0.009), and negatively associated with VBAC rates (β = −0.35, P = 0.01). These estimates imply that a $10,000 decrease in premiums for obstetrician-gynecologists would be associated with an increase of 0.35 percentage points (1.45%) in the VBAC rate and decreases of 0.15 and 0.16 percentage points (0.7% and 1.18%) in the rates of cesarean section and primary cesarean section, respectively; this would correspond to approximately 1600 more VBACs, 6000 fewer cesarean sections, and 3600 fewer primary cesarean sections nationwide in 2003. Two types of tort reform—caps on noneconomic damages and pretrial screening panels—were associated with lower rates of cesarean section and higher rates of VBAC. CONCLUSIONS: The liability environment influences choice of delivery method in obstetrics. The effects are not large, but reduced litigation pressure would likely lead to decreases in the total number cesarean sections and total delivery costs.